FOLR2+ macrophages in cancer: allies or enemies - Decheng Jiang; Ruiling Xiao; Jialu Bai; Xing Wang; Yuan Fang; Jianzhou Liu; Xiaohan Wang; Ming Cui; Lei You; Yupei Zhao (Cell Communication and Signaling, 2025)
Abstract The advent of the omics era has facilitated the identification of precise biomarkers for cancer progression, revealing a broader diversity of macrophage phenotypes beyond the traditional M1/M2 classification. Folate receptor 2 (FOLR2)-positive macrophages, co-expressing markers such as mannose receptor C-Type 1 (MRC1/CD206) and lymphatic vessel endothelial hyaluronan receptor 1(LYVE1), are an embryonically derived subset typically found around blood vessels in both tumor stroma and normal tissues. Despite FOLR2’s longstanding association with anti-inflammatory, immunosuppressive macrophages in tumors, its precise role in cancer progression remains unclear. Recent studies suggest that FOLR2+ macrophages can either promote or inhibit cancer progression, depending on their multifaceted roles in the tumor microenvironment. This review provides a comprehensive overview of the biological features, functional roles, molecular mechanisms, and therapeutic potential of FOLR2+ macrophages in cancer.